Medication against Conflict - Andrea Berlanda; Matteo Cervellati; Elena Esposito; Dominic Rohner; Uwe Sunde (Center for Economic Studies and ifo Institute (CESifo), 2022)
The consequences of successful public health interventions for social violence and conflict are largely unknown. This paper closes this gap by evaluating the effect of a major health intervention – the successful expansion of anti-retroviral therapy (ART) to combat the HIV/AIDS pandemic – in Africa. To identify the effect, we combine exogenous variation in the scope for treatment and global variation in drug prices. We find that the ART expansion significantly reduced the number of violent events in African countries and sub-national regions. The effect pertains to social violence and unrest, not civil war. The evidence also shows that the effect is not explained by general improvements in economic prosperity, but related to health improvements, greater approval of government policy, and increased trust in political institutions. Results of a counterfactual simulation reveal the largest potential gains in countries with intermediate HIV prevalence where disease control has been given relatively low priority.
Keywords: C36; D47; I15; O10; 330; HIV; conflict; social violence; ART expansion; trust; Africa; health intervention; domestic violence